SOME ASPECTS OF EFL READING COMPREHENSION - Calixto, Benedito José (Revista Expectativa, 2000)
The ability to read with understanding is an essential skill in modern society. However, many people may never manage to read well. Many people face some daily reading tasks lacking confidence in their own ability. Reading in English as a foreign language can be considered the most necessary skill in Brazil. It is used in many ways as general and specific purposes.